2004
DOI: 10.1111/j.1365-2125.2004.02113.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenotyping and genotyping study of thiopurine S‐methyltransferase in healthy Chinese children: A comparison of Han and Yao ethnic groups

Abstract: AimsEthnicity is an important variable influencing drug response. Thiopurine S-methyltransferase (TPMT) plays an important role in the metabolism of thiopurine drugs. Previous population studies have identified ethnic variations in both phenotype and genotype of TPMT , but limited information is available within Chinese population that comprises at least 56 ethnic groups . The current study was conducted to compare both phenotype and genotype of TPMT in healthy Han and Yao Chinese children. MethodsTPMT activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 33 publications
2
27
1
Order By: Relevance
“…Among variant TPMT alleles, the TPMT*3A allele was the most common, followed by the TPMT*3C and TPMT*2 alleles. Several studies have established interethnic differences in the frequencies of TPMT alleles, with the TPMT*3A and TPMT*2 alleles most common in Caucasians and the TPMT*3C allele most common in individuals of black or Asian ethnicity (33)(34)(35). In our population, the ethnicities were not known; therefore, the allelic frequencies reported here are representative only of a US-based diverse population.…”
Section: Discussionmentioning
confidence: 93%
“…Among variant TPMT alleles, the TPMT*3A allele was the most common, followed by the TPMT*3C and TPMT*2 alleles. Several studies have established interethnic differences in the frequencies of TPMT alleles, with the TPMT*3A and TPMT*2 alleles most common in Caucasians and the TPMT*3C allele most common in individuals of black or Asian ethnicity (33)(34)(35). In our population, the ethnicities were not known; therefore, the allelic frequencies reported here are representative only of a US-based diverse population.…”
Section: Discussionmentioning
confidence: 93%
“…TPMT*2 is one of the three common mutant alleles which are generally confined to Caucasians and Latin American populations, with allele frequency of 0.2-0.7% [19,20,25,26]. Besides the interethnic variability, studies indicated that populations within the same ethnic origin can demonstrate significant differences in the distribution of common defective alleles [27]. For example, Wei et al recently reported that Kazak population, which is Caucasian in ethnic origin, has a very distinct pattern and lower frequency distribution for common TPMT mutant alleles compared to other Caucasians [28].…”
Section: Introductionmentioning
confidence: 98%
“…The frequency distribution of TPMT enzyme activity in the Caucasian population is trimodal, such that wild-type homozygotes (TPMT*1) have high enzyme activity (89.5%), while heterozygous and homozygous individuals for TPMT*2, TPMT*3A and TPMT*3C alleles show intermediate and low enzyme activity (9.9 and 0.6%, respectively) [12] . Such a distribution has not been found in non-Caucasian populations [17][18][19][20][21] . Individuals with intermediate or defi cient TPMT activity thus have a higher risk for toxic events such as life-threatening myelosuppression and/or secondary tumor development after receiving standard doses of thiopurine drugs [22] .…”
mentioning
confidence: 99%